Effect of aging on audiovisual integration: Comparison of high- and low-intensity conditions in a speech discrimination task - Yang, Weiping; Guo, Ao; Yao, Hanyun; Yang, Xiangfu; Li, Zimo; Li, Shengnan; Chen, Jianxin; Ren, Yanna; Yang, Jiajia; Wu, Jinglong; Zhang, Zhilin (Frontiers in Aging Neuroscience, 2022)
Audiovisual integration is an essential process that influences speech perception in conversation. However, it is still debated whether older individuals benefit more from audiovisual integration than younger individuals. This ambiguity is likely due to stimulus features, such as stimulus intensity. The purpose of the current study was to explore the effect of ageing on audiovisual integration, using event-related potentials (ERPs) at different stimulus intensities. The results showed greater audiovisual integration in older adults at 320-360 ms. Conversely, at 460-500 ms, older adults displayed attenuated audiovisual integration in the frontal, fronto-central, central and centro-parietal regions compared to younger adults. In addition, we found older adults had greater audiovisual integration at 200-230 ms under the low-intensity condition compared to the high-intensity condition, suggesting inverse effectiveness occurred. However, inverse effectiveness was not found in younger adults. Taken together, the results suggested that there was age-related dissociation in audiovisual integration and inverse effectiveness, indicating that the neural mechanisms underlying audiovisual integration differed between older adults and younger adults.